2012
DOI: 10.1002/jbm.a.34241
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 tethered hydroxyapatite for bone tissue regeneration: Coating chemistry and osteoblast attachment

Abstract: The goal of this study was to determine the effectiveness of using polyethyleneimine (PEI) and a polyethylene glycol (PEG) tether to bind human recombinant bone morphogenetic protein‐2 (rhBMP‐2) to hydroxyapatite (HAp) to enhance rhBMP‐2 loading, alter its release properties, and enhance cellular interaction with the material. By using a branched PEI that was derived to express free thiols, rhBMP‐2 was coated onto dense HAp surfaces at ∼43 ng/cm2. Using this novel attachment methodology, it was observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Cell attachment was dependent on the identity of the printed proteins and also the solution concentration used for printing. Both Coll I and BMP 2 were shown to facilitate cell capture, correlating with other studies [3,8,[52][53][54]. On spots printed with low protein content formulations, cell attachment was observed to be poor.…”
Section: Discussionsupporting
confidence: 68%
“…Cell attachment was dependent on the identity of the printed proteins and also the solution concentration used for printing. Both Coll I and BMP 2 were shown to facilitate cell capture, correlating with other studies [3,8,[52][53][54]. On spots printed with low protein content formulations, cell attachment was observed to be poor.…”
Section: Discussionsupporting
confidence: 68%
“…If required, the initial release of BMP2 from hollow HA microspheres can be optimized by adjusting either the amount of BMP2 loaded, the composition and structure of the HA with varying amounts of carbonate substitution, or tethering other polymer materials. 17 This study also showed that BMP2-loaded hollow HA microspheres had a high capacity to regenerate bone in vivo, when compared to hollow HA microspheres without BMP2 or soluble BMP2 without a carrier. As early as 4 weeks, we …”
Section: Discussionmentioning
confidence: 51%
“…Among them, hydroxyapatite (HA) has shown several striking advantages over other carriers for BMP2 delivery to regenerate large bone defects. 10,[16][17][18][19] HA is a bioactive ceramic with chemical composition similar to the mineral component of bone, which accounts for its excellent biocompatibility and osteoconductivity. [20][21][22] HA has been used in bone repair for bone augmentation, coating implants, and as bone filler.…”
mentioning
confidence: 99%
“…These features allow the material to present a geometric configuration similar to natural bone and, according to Ripamonti et al (12), allow this material to adsorb the bioactive proteins and the grow factors concentrated in the clot. It allows the progressive releasing of these factors, able to induce migration, adhesion and proliferation of cells inside the pore network and to promote a faster angiogenesis and a more effective osteo-genesis inside these pores (19)(20)(21). Theoretical data was confirmed by clinical outcome (22).…”
Section: Discussionmentioning
confidence: 92%